Oxidative stress in the blood of patients with active localized vitiligo - Arican, Ozer (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Objectives: Vitiligo is an acquired skin disease characterized by white areas on the skin. The pathogenesis of the disease is still unclear. Some findings show that oxidative stress could be an important phenomenon in the pathophysiology of vitiligo. Methods: We evaluated 16 consecutive localized vitiligo patients and 16 healthy controls of a similar age and sex distribution. We measured their indicators of oxidative stress such as catalase (CAT), superoxide dismutase (SOD), glucose 6-phosphate dehydrogenase (G6PD) in erythrocytes, and plasma malondialdehyde (MDA) by spectrophotometry.Results: SOD activities and MDA levels of patients were significantly higher than controls (p < 0.001). CAT and G6PD activities of patients were significantly lower than controls (p < 0.05 and p < 0.001, respectively). Conclusion: Our results confirmed that oxidative stress may play an important role in the pathogenesis of vitiligo. Melanocyte damage in vitiligo might be linked to generalized oxidative stress. This study is the first report on some antioxidant parameters of localized-type vitiligo patients.
Keywords: Antioksidanti; antioxidant; Antioxidants; Catalase; dermatologija; Glucosephosphate Dehydrogenase; Glukozofosfatna dehidrogenaza; Katalaza; Malondialdehid; Malondialdehyde; Oksidativni stres; Oxidative Stress; patogeneza; Superoksidna dismutaza; Superoxide Dismutase; Vitiligo